The Influence of Learning MethodsDrill And Practice On the Material of Computer Number Systems on the Learning Outcomes of Class X Students of State Vocational School 6 Kupang - Dangut, Theresia Avila; Sogen, Maria M. B.; Fallo, Diana Y. A. (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to determine whether there is an effect of the drill and practice method on the computer number system material on the learning outcomes of class X students of SMK Negeri 6 Kupang in the 2024/2025 academic year. This type of research is an experiment with a quasi-experimental design, the population in this study were all students of class X of the Software and Game Program (PPLG) of SMK Negeri 6 Kupang, while the sample used was class X PPLG 1 students as a control class totaling 28 people and class X PPLG 2 students as an experimental class totaling 32 people. The results of the study obtained from the analysis showed that the average value of learning outcomes for the computer number system material taught using the drill and practice method was 68.44 and the value of students taught using conventional learning methods had an average value of 53.57. In testing the hypothesis using the t-test, namely the independent samples test with a t-count value of 0.000 <0.05. So the proposed hypothesis is accepted, there is a significant influence of the drill and practice learning method on the computer number system material on the learning outcomes of class X students of SMK Negeri 6 Kupang in the 2024/2025 academic year.